2014
DOI: 10.1111/all.12462
|View full text |Cite
|
Sign up to set email alerts
|

Immunoproteomics of processed beef proteins reveal novel galactose‐α‐1,3‐galactose‐containing allergens

Abstract: We show that the α-Gal epitope is commonly present in IgE-reactive beef proteins recognized by meat-allergic patients. Seven novel α-Gal-containing IgE-binding proteins were identified, of which four were stable to heat treatment. Thus, the allergenicity of red meat proteins is preserved even upon different thermal cooking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 32 publications
1
69
0
2
Order By: Relevance
“…We used our study cohort to identify α‐gal‐carrying proteins in beef because to the best of our knowledge, only five sera from patients with α‐gal‐mediated delayed meat allergy have been employed to address this question so far 30. Those patients showed multiple but overall faint bands in immunoblots.…”
Section: Discussionmentioning
confidence: 99%
“…We used our study cohort to identify α‐gal‐carrying proteins in beef because to the best of our knowledge, only five sera from patients with α‐gal‐mediated delayed meat allergy have been employed to address this question so far 30. Those patients showed multiple but overall faint bands in immunoblots.…”
Section: Discussionmentioning
confidence: 99%
“…Bands in mass range of 5–10, 10–15 and 15–20 kDa were subjected to in gel digestion and MS analysis on EASY nanoLC II system coupled with LTQ Orbitrap XL (Thermo Fisher Scientific Inc., Bremen, Germany), previously calibrated with the ProteoMass ™ LTQ/FT-Hybrid ESI Positive Mode Cal Mix (MSCAL5 SUPELCO, Sigma-Aldrich) as described previously 19 . The experiments were performed in duplicate.…”
Section: Methodsmentioning
confidence: 99%
“…Some of these proteins remain stable to thermal processing, showing that the allergenic properties are preserved in cooked meat 19, 20 . The long delay of symptoms in α-Gal allergy raises the question whether α-Gal glycoproteins have a retained IgE reactivity and allergenic properties when they appear in the circulation after digestion.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, evidence has come from a study examining beef extracts using 2D gel electrophoresis. The authors demonstrated seven alpha-gal containing IgE binding proteins, four of which survived heating the beef extract 17 . How alpha- gal is structurally expressed on red meat remains unclear.…”
Section: The Red Meat Connectionmentioning
confidence: 99%